Gastric adenocarcinoma arising from hamartomatous inverted polyp during 8‐year follow‐up. Issue 1 (22nd August 2021) - Okamura, Takuma; Iwaya, Yugo; Nagaya, Tadanobu; Muranaka, Futoshi; Ota, Hiroyoshi; Umemura, Takeji
Abstract: Gastric hamartomatous inverted polyp (GHIP) is rare, with few reports of carcinogenesis from GHIP during long‐term follow‐up. A 51‐year‐old woman was diagnosed as having a submucosal tumor (SMT) during esophagogastroduodenoscopy (EGD) in 2008. In 2016, although the size and height of the lesion had not changed, she was referred to our hospital for further investigation of the lesion. EGD depicted a gastric SMT of 20 mm in diameter in the greater curvature of the upper gastric body, and a biopsy specimen showed a well to poorly differentiated adenocarcinoma. Following successful laparoscopic total gastrectomy, histopathological examination revealed an intramucosal adenocarcinoma arising in GHIP.